HUBUNGAN PENGETAHUAN IBU NIFAS TENTANG PERAWATAN PAYUDARA DENGAN KELANCARAN ASI DI PMB BIDAN E TAHUN 2022 - Azis, Aninditya (Politeknik Tiara Bunda, 2022)
Background: Mother's milk is useful as nutritional intake and also maintains the baby's body resistance. The problem that occurs is the irregularity of breast milk production in postpartum mothers. Purposed: To determine the effect of consuming green beans on increasing breast milk production in postpartum mothers in PMB D, Bandung Regency in 2024. Methods: The research design uses a quasi experiment with a pretest posttest approach with control group design. A population of 30 people using a purposive sampling technique resulted in a sample of 15 people in the experimental group and 15 people in the control group. The research instrument used an observation sheet for breast milk expenditure. Data analysis was univariate with frequency distribution and bivariate using the Mann Whitney test. Results: Most breast milk production in postpartum mothers before consuming green beans was low (86.75%) and after consuming green beans most breast milk was abundant (73.3%). Breast milk production among postpartum mothers who did not consume green beans before the intervention was mostly insufficient breast milk (80%) and after the intervention most breast milk was sufficient (53.3%). There is a difference in breast milk production between postpartum mothers who consume green beans and those who do not consume green beans in PMB D (p-value 0.000 < 0.05). Conclusion: Consuming green beans can increase breast milk production in postpartum mothers